2021
DOI: 10.1002/aic.17458
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the dependence of CO2 activation on hydrogen dissociation ability over supported nickel catalysts

Abstract: In the present work, we demonstrate that the mechanism and kinetics of CO 2 activation, as the first step of its hydrogenation, over supported nickel catalysts is particle size sensitive owing to the distinct H 2 dissociation ability over nickel particles with various sizes. Large nickel nanoparticles facilitate H 2 dissociation, enabling CO 2 activation via a kinetically favored redox mechanism compared to small nickel nanoparticles that activate CO 2 via the formate mechanism. The elucidation of the dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…For the fresh 40NiAl catalyst (Figure a), the reduction peak shifts to lower temperatures with a T p of 410 °C and an onset temperature of 271 °C. Such a shift has been previously ascribed to possessing larger nickel nanoparticles and improved hydrogen dissociation ability for 40NiAl than 10NiAl . The content of reduced Ni species in Ni/Al 2 O 3 is quantified using CuO as an external standard.…”
Section: Resultsmentioning
confidence: 98%
“…For the fresh 40NiAl catalyst (Figure a), the reduction peak shifts to lower temperatures with a T p of 410 °C and an onset temperature of 271 °C. Such a shift has been previously ascribed to possessing larger nickel nanoparticles and improved hydrogen dissociation ability for 40NiAl than 10NiAl . The content of reduced Ni species in Ni/Al 2 O 3 is quantified using CuO as an external standard.…”
Section: Resultsmentioning
confidence: 98%
“…56,57 The bands at1441 and 1528 cm −1 could be assigned to carbonate [ν s (CO 3 − )] and bicarbonate [ν a (CO)] species due to the interaction of adsorbed CO 2 with H*. 56,58,59 This demonstrated that acetone is degraded to formic acid first and then formic acid is decomposed to carbonate and bicarbonate species on 12CoCu-R. Finally, CO 2 and H 2 O are formed through complete oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The incomplete reduction of Ni 2+ to Ni 0 at 600 °C could explain the low CO 2 conversion and poor productivity below 375 °C. A higher number of Ni 0 sites after reduction at 750 °C may increase both the activation of CO 2 by the dissociative mechanism and the H 2 splitting and, therefore, the CH 4 productivity . Hence, the following Mg-containing catalysts are prereduced in situ at 750 °C.…”
Section: Resultsmentioning
confidence: 99%